Effects of neuromuscular training and electrical stimulation on ankle stability and muscle strength of peroneus longus in rock climbers - Saleephon, Khingkhan; Boonyaroma, Onuma; Jorrakate, Chaiyong (Chulalongkorn Medical Journal, 2020)
Background: Ankle sprains during rock climbing are caused by several factors, such as landing on the ground and footing while climbing. Additionally, ankle sprains involved with the footing are often due to rock climbing shoes. These shoes are often restricting the motion of the feet, resulting in the shortening of the toe and ankle muscles in supination, which leads to a higher risk for an ankle sprain. Investigating neuromuscular training and electrical stimulation are necessary for the development of an effective training of the ankles to prevent injury. Objectives: To study the effects of neuromuscular training and electrical stimulation on ankle stability and muscle strength of the peroneus longus (PL) in rock climbers. Methods: Sixteen rock climber volunteers of 18 - 30 years old were tested for the isometric muscle strength of their PL muscle and ankle stability while moving. The subjects were divided into two groups of eight people: Group 1 performed functional ankle training on a wobble board (WB) (n = 8), and Group 2 did similar but with additional neuromuscular electrical stimulation (NMES) (n = 8). The groups were trained 3 days a week for 4 weeks. Results: The results showed that within the WB and WB+NMES groups after 4 weeks training, there was a significant increase in the PL muscle strength and the stability of the ankle while moving (P < 0.05). However, there was no significant difference between the groups themselves. Conclusion: This study concluded that the training program for both groups could increase the PL muscle strength and the stability of the ankle while moving.